2016
DOI: 10.31686/ijier.vol4.iss7.573
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Murabaha in Islamic Banks

Abstract: After the collapse of the Islamic Caliphate in Istanbul and the loss of the First World War, Shari'a and Arabic as the law and language of the Muslim world were replaced with common laws and numerous European languages were introduced into the new Arab states. These events led to calls for reestablishing the shari’a for all aspects of life. Arab countries responded by constituting Islamic parties and institutions including Islamic banks. Islamic banks flourished quickly all over the world. Some consider this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The results found that IBs indices generally outperform in developed markets but underperform in emerging markets.Elgadi, Entissar, M. (2016) investigated the interrelationship between performance, measures and determinants of SudaneseIBs (2005IBs ( -2013. The estimated results of the model prove that PLS role of Modaraba and Mosharaka have a significant positive impact on profitability Mansour, I. and Sa'adeh, Y. (2016).…”
mentioning
confidence: 68%
“…The results found that IBs indices generally outperform in developed markets but underperform in emerging markets.Elgadi, Entissar, M. (2016) investigated the interrelationship between performance, measures and determinants of SudaneseIBs (2005IBs ( -2013. The estimated results of the model prove that PLS role of Modaraba and Mosharaka have a significant positive impact on profitability Mansour, I. and Sa'adeh, Y. (2016).…”
mentioning
confidence: 68%
“…On the other hand, the Muslim community also has serious concerns regarding the practices of Murabaha financing as they think there is no difference exist between conventional and Islamic financing as the study by Mansour and Sa'adeh (2016) to analyze and investigate the practices of the Islamic banks with regard to the shari'a point of view. The finding suggests that practices of Murabaha financing, which is thought to be according to the Islamic financing principles, are far from Sharia complaints and principles (Mansour & Sa'adeh, 2016). So, it is crucial for all the banks who claim the There are some limitations related to the Murabaha Sukuk as in the Islamic financing\g someone cannot sell the commodity without getting the possession of a assets (Morni, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Murabahah: Mansour and Sa'adeh (2016) state that in a murabahah transaction, cooperative buys the item required by the user and sells it at a profit to the user with the payment deferred to a date agreed by the parties. The payment is normally made in instalments.…”
Section: Sources and Application Of Funds (Financial Resources) In Islamic Cooperativesmentioning
confidence: 99%